Comparative Effectiveness of Medical Therapy, Supervised Exercise, and Revascularization for Patients With Intermittent Claudication: A Network Meta‐analysis - Vemulapalli, Sreekanth (Clin Cardiol, 2015)
BACKGROUND: There are limited data on the comparative effectiveness of medical therapy, supervised exercise, and revascularization to improve walking and quality of life in patients with intermittent claudication (IC). HYPOTHESIS: Supervised exercise and revascularization was superior to medical therapy in IC. METHODS: We studied the comparative effectiveness of exercise training, medications, endovascular intervention, and surgical revascularization on outcomes including functional capacity (walking distance and timing), quality of life, and mortality. We searched PubMed, EMBASE, and the Cochrane Database of Systematic Reviews from January 1995 to August 2012 for relevant English‐language studies. Two investigators independently collected data. Meta‐analyses with random‐effects models of direct comparisons were supplemented by mixed‐treatment analyses to incorporate data from placebo comparisons, head‐to‐head comparisons, and multiple treatment arms. RESULTS: Thirty‐five unique studies evaluated treatment modalities in 7475 patients with IC. Compared with usual care, only exercise training improved both maximal walking distance (150 meters; 95% confidence interval: 35–266 meters, P = 0.01) and initial claudication distance (39 meters; 95% confidence interval: 9–65 meters, P = 0.003). All modalities were associated with improved quality of life (Short Form‐36 physical functioning score) compared with usual care, but there were no differences between treatments. There were insufficient safety data to assess treatment‐related complications. All‐cause mortality was not significantly different between modalities. CONCLUSIONS: Evidence is insufficient to determine treatment superiority for improving quality of life and walking parameters in IC patients. Further studies with attention to study design, standardized efficacy and safety endpoints, and appropriate subgroup reporting are necessary to determine comparative effectiveness.